2022
DOI: 10.1111/bjh.18098
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of post‐partum haemorrhage risk among women with moderate thrombocytopenia

Abstract: Summary It is unknown whether moderate thrombocytopenia represents a risk factor for post‐partum haemorrhage (PPH). We assessed PPH risk among women with a platelet count of between 100 and 50 × 109/l and stratified the risk for O/non‐O blood group. We included consecutive women undergoing vaginal delivery or caesarean section with moderate thrombocytopenia. Women with >150 × 109/l platelets at delivery were selected as controls and matched for age, type of birth and ethnicity. Odds ratios (ORs) with their 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A study of 1,085 women with twin gestations found a greater incidence of PPH in women with mild thrombocytopenia compared with those with normal platelet count ( 10 ). Additionally, moderate thrombocytopenia ( 22 ) and severe thrombocytopenia ( 8 ) were also convinced to be risk factors for PPH in twin pregnancies. Based on these findings, ( 8 , 10 , 22 ) a conclusion that thrombocytopenia in pregnancy was associated with PPH regardless of its severity could be deduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 1,085 women with twin gestations found a greater incidence of PPH in women with mild thrombocytopenia compared with those with normal platelet count ( 10 ). Additionally, moderate thrombocytopenia ( 22 ) and severe thrombocytopenia ( 8 ) were also convinced to be risk factors for PPH in twin pregnancies. Based on these findings, ( 8 , 10 , 22 ) a conclusion that thrombocytopenia in pregnancy was associated with PPH regardless of its severity could be deduced.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, moderate thrombocytopenia ( 22 ) and severe thrombocytopenia ( 8 ) were also convinced to be risk factors for PPH in twin pregnancies. Based on these findings, ( 8 , 10 , 22 ) a conclusion that thrombocytopenia in pregnancy was associated with PPH regardless of its severity could be deduced. In addition, our study demonstrated that gestational thrombocytopenia was indeed more common in women with PPH.…”
Section: Discussionmentioning
confidence: 99%
“…PPH is defined as primary if the bleeding occurs before delivery of the placenta and up to 24 h after delivery of the fetus, or secondary if it occurs more than 24 h after delivery 9 . PPH risk factors include antepartum haemorrhage, augmented or induced labour, instrumental or caesarean delivery, chorioamnionitis, foetal macrosomia, polyhydramnios, maternal anaemia, thrombocytopenia or hypofibrinogenaemia, maternal obesity, multifetal gestation, preeclampsia, prolonged labour, placentation abnormalities and older age 18–25 . Hereditary haemostatic disorders and a history of PPH in a previous delivery also increase the risk 20,26,27 .…”
Section: Causes and Pathophysiology Of Postpartum Haemorrhagementioning
confidence: 99%
“…9 PPH risk factors include antepartum haemorrhage, augmented or induced labour, instrumental or caesarean delivery, chorioamnionitis, foetal macrosomia, polyhydramnios, maternal anaemia, thrombocytopenia or hypofibrinogenaemia, maternal obesity, multifetal gestation, preeclampsia, prolonged labour, placentation abnormalities and older age. [18][19][20][21][22][23][24][25] Hereditary haemostatic disorders and a history of PPH in a previous delivery also increase the risk. 20,26,27 However, it is estimated that about 40% of PPH cases occur in women who do not have any risk factors, emphasising the importance of surveillance in all women.…”
Section: Causes and Pathophysiology Of Postpartum Haemorrhagementioning
confidence: 99%
“…Type O blood has been shown in the trauma literature to be associated with lower rates of von Willebrand factor (VWF), but whether type O blood increases the risk of PPH has not been confirmed, particularly for patients whose pregnancy is also complicated by thrombocytopenia. In a multicenter cohort study of 188 patients, 32 consecutive patients delivering with moderate or severe thrombocytopenia or immune thrombocytopenia purpura (mean platelet count, 90 000) were matched by age, mode of delivery, and ethnicity to controls with normal platelet counts. The authors found in their primary analysis that the adjusted risk of PPH associated with type O blood was stronger in patients with thrombocytopenia (aOR, 12.7; 95% CI, 2.9-55.3) than in patients without thrombocytopenia (aOR, 3.2; 95% CI, 1.1-9.5).…”
Section: Pertaining To Disparities In Hemorrhage By Conditionmentioning
confidence: 99%